(untitled) (Research, Society and Development, 2021)
This work aims to investigate academic production involving scientific dissemination (SD) in the initial education of undergraduate Chemistry students, analyzing their objectives when using SD, advantages, limitations and gaps on the theme and perspectives. It´s a descriptive and exploratory research and the database was the Brazilian Digital Library of Theses and Dissertations (BDTD), in the period from 2010 to 2020. The selection of works took place in two stages, title and summary reading, and for those selected, full assessment and descriptive analysis were performed. The work develops the idea that SD is a resource that can contribute in different aspects to teacher education and favor a more adequate view of the scientific knowledge production process. We believe that the SD has potential for Chemistry teaching and when it is inserted in the classroom, it favors a more adequate view on the science production process. We emphasize the need for more works that investigates SD in the teaching of Chemistry.